The Quality of the Legal System, Firm Ownership, and Firm Size - Laeven, Luc; Woodruff, Christopher (World Bank, Washington, D.C., 2013)
Employment in developing countries is disproportionately concentrated in very small firms. The authors examine the extent to which the distribution of firm size is related to the quality of the legal system using data from Mexico. They combine Lucas' (1978) model of firm size with Himmelberg, Hubbard, and Love's (2001) consideration of idiosyncratic risk in a framework in which the distribution of entrepreneurial talent and aversion to idiosyncratic risk combine to determine the optimal size of firms. Their data allows them to focus on the differential impact of the legal system on proprietorships and corporations. Moreover, by focusing on firms in a single country, the data draw attention to the importance of variation in the administration of justice and the enforcement of legal verdicts. The authors find that Mexican states with more effective legal systems have larger firms. A one-standard deviation improvement in the quality of the legal system increases the average firm size by about 10-15 percent. The impact of the legal system is greatest in sectors in which proprietorships dominate. This pattern is consistent with better legal systems increasing the investment of firm owners by reducing the idiosyncratic risk they face. All of these findings are upheld when the authors instrument for institutional variables using the log of indigenous population in 1900 and the active presence of the drug trade in the state.